Jamaah Tabligh: antara Spiritualitas Tradisional dan Tantangan Dakwah Kontemporer - Susanto, Dedi; Fajri , Ahmad Khairul; Kuswiyanto (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study explores the origin, contributions, and relevance of the Tablighi Jamaat within the contemporary development of Islamic da'wah. Using a qualitative approach and literature-based method, the study reveals that Tablighi Jamaat, founded by Maulana Muhammad Ilyas in early 20th century India, is a revivalist movement focused on spiritual reform and personal outreach. Its contribution lies in promoting Islam through a non-confrontational, mosque-centered method that emphasizes direct engagement with individual Muslims across various countries. In the modern era, the movement remains relevant by preserving individual piety amidst growing secularization and globalization. However, its limited engagement with socio-political issues remains a major critique.